2005
DOI: 10.1158/0008-5472.can-04-4391
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Therapeutic Efficacy of Taxol by the Mitogen-Activated Protein Kinase Kinase Inhibitor CI-1040 in Nude Mice Bearing Human Heterotransplants

Abstract: Taxol may contribute to intrinsic chemoresistance by activating the mitogen-activated protein kinase kinase (MEK)/ extracellular signal-regulated kinase (ERK) cytoprotective pathway in human cancer cell lines and tumors. We have previously shown additivity between Taxol and the MEK inhibitor, U0126 in human cancer cell lines. Here, the combination of Taxol with an orally bioavailable MEK inhibitor, CI-1040, was evaluated in human lung tumors heterotransplanted into nude mice. Unlike xenograft models that are d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 49 publications
6
64
0
Order By: Relevance
“…Paclitaxel activates the MEK/ERK pathway and compromises its own activity, which activates apoptosis via the c-Jun NH 2 -terminal kinase pathway. Enhancement of the therapeutic efficacy of Taxol by CI-1040 has also been shown in nude mice bearing human non -small cell lung cancer heterotransplants (31). CI-1040 alone increased the expression of S473-phosphorylated Akt in several of these heterotransplants, whereas the concurrent combination of CI-1040 and Taxol resulted in lower S473-phosphorylated Akt, suggesting that inhibition of MEK can reciprocally activate Akt.…”
Section: Azd6244 An Inhibitor Of Mek1/2 Kinasesmentioning
confidence: 75%
“…Paclitaxel activates the MEK/ERK pathway and compromises its own activity, which activates apoptosis via the c-Jun NH 2 -terminal kinase pathway. Enhancement of the therapeutic efficacy of Taxol by CI-1040 has also been shown in nude mice bearing human non -small cell lung cancer heterotransplants (31). CI-1040 alone increased the expression of S473-phosphorylated Akt in several of these heterotransplants, whereas the concurrent combination of CI-1040 and Taxol resulted in lower S473-phosphorylated Akt, suggesting that inhibition of MEK can reciprocally activate Akt.…”
Section: Azd6244 An Inhibitor Of Mek1/2 Kinasesmentioning
confidence: 75%
“…One defined outcome was the activation of ERK1/2 signaling, and this event may be associated with the redistribution of PKCq following docetaxel treatment. Indeed, it has been reported that 20% to 40% of ERK1/2 is localized to the microtubules (17) and the redistribution of PKCq may enable this activation to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Initially described as antimitotic agents, taxanes bind to h-tubulins and stabilize the microtubular network, thus resulting in the block of the cell cycle at G 2 -M and subsequent apoptosis of the cells (16,17). Previous studies have shown that taxanes may also inappropriately induce activation of prosurvival signaling pathways such as Ras-Rafmitogen-activated protein kinase/extracellular signal -regulated kinase (ERK) kinase-ERK, leading to cancer cell resistance (16,17), and we have reported that inhibition of ERK1/2 sensitized melanoma cells to docetaxel-induced apoptosis (18). The mechanism of activation of the ERK1/2 pathway by taxanes, however, is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these considerations, there has been intense interest in developing low molecular weight pathway specific MAPK inhibitors as therapeutic agents to treat cancer and fibroproliferative inflammatory conditions (Duncia et al 1998;Sebolt-Leopold et al 1999;Clemons et al 2002;Duan et al 2004;Sebolt-Leopold and Herrera 2004;Jo et al 2005;McDaid et al 2005). These agents have been employed in experimental renovascular disease, with mixed results.…”
Section: Mapk Pathways and Renovascular Diseasementioning
confidence: 99%